Gram Stain-Specific-Probe-Based Real-Time PCR for Diagnosis and Discrimination of Bacterial Neonatal Sepsis - Wu, Yi-Dong; Chen, Li-Hua; Wu, Xiu-Jing; Shang, Shi-Qiang; Lou, Jin-Tu; Du, Li-Zhong; Zhao, Zheng-Yan (Journal of Clinical Microbiology, 2008)
Sepsis is a serious disease with high mortality in newborns. It is very important to have a convenient and accurate method for pathogenic diagnosis of neonatal sepsis. We developed a method of simultaneous detection and Gram classification of clinically relevant bacterial pathogens causing sepsis directly from blood samples with Gram stain-specific-probe-based real-time PCR (GSPBRT-PCR). With GSPBRT-PCR, 53 clinically important strains representing 25 gram-positive and 28 gram-negative bacterial species were identified correctly with the corresponding Gram probe. The limits of the GSPBRT-PCR assay in serial dilutions of the bacteria revealed that Staphylococcus aureus could be detected at concentrations of 3 CFU per PCR and Escherichia coli at concentrations as low as 1 CFU per PCR. The GSPBRT-PCR assay was further evaluated on 600 blood specimens from patients with suspicioon of neonatal sepsis and compared to the results obtained from blood cultures. The positive rate of the GSPBRT-PCR array was 50/600 (8.33%), significantly higher than that of blood culture (34/600; 5.67%) (P = 0.00003). When blood culture was used as a control, the sensitivity of GSPBRT-PCR was 100%, the specificity was 97.17%, and the index of accurate diagnosis was 0.972. This study suggests that GSPBRT-PCR is very useful for the rapid and accurate diagnosis of bacterial infection and that it can have an important impact on the current inappropriate and unnecessary use of antibiotics in the treatment of newborns.